Estudantes universitários de uma instituição privada e suas relações com o saber : de espectadores a protagonistas - Vieira, Karina Sales (2017)
The study aims to analyze the relationships with the knowledge of university students entering a private institution in the interior of Bahia through the assistance of government programs such as the Student Funding Fund (FIES) and the University for All Program (ProUni) and even those implemented by the institution itself, such as the Host Program (ProVIDA). The Institution object of this research is the first higher education institution of the municipality of Paripiranga (BA), region included in the Polygon of dry and located 360km from Salvador and 110km from Aracaju. In order to reach the proposed objective, the subjects of the research were 170 undergraduate university students of the first and second periods, all of them scholarship holders of the Programs indicated above and having joined the Institution in 2015/2016. As instruments of data production a questionnaire, the Balance of Knowledge, and interview were adopted. The research is based on a qualitative investigation and the works of Bernard Charlot and Alain Coulon as the main references that support the discussions explored here.The study pointed to a profile of students young, female, from low-income classes, who exceeded their parents' schooling and arrived at university. The relationship with the academic knowledge for these university students is marked by the desire to, from the diploma, to enter the labor market and thus to grow economically. In this context, it seems that the University fulfills its role, since more than half of them mention intellectual knowledge when referring to the learning they acquired at the University, although they have not been able to specify a content, a knowledge. The University for students is also visualized and experienced as a space far from its reality, the space of new experiences, of meeting new people, establishing different relationships.